Curcumin prevents osteocyte apoptosis by inhibiting M1‐type macrophage polarization in mice model of glucocorticoid‐associated osteonecrosis of the femoral head. Issue 9 (13th February 2020) - Jin, Shengyang; Meng, Chunqing; He, Yu; Wang, Xiaohong; Zhang, Qimin; Wang, Ze; Huang, Wei; Wang, Hong
Abstract: Inflammation is a contributing factor in osteocyte apoptosis, which is strongly associated with the development of glucocorticoid‐associated osteonecrosis of the femoral head (GA‐ONFH). Curcumin is a naturally derived drug that regulates immunity and inhibits inflammation. This study aimed to examine the capacity of curcumin to prevent osteocyte apoptosis and GA‐ONFH, while elucidating possible mechanisms of action. C57/BL6 female mice were divided into control, GA‐ONFH, and curcumin‐treated GA‐ONFH groups. We determined the effect of curcumin on the polarization of RAW264.7 and the apoptosis of MLO‐Y4 cells. We found that curcumin reduced the infiltration of M1‐type macrophages in the femoral heads and alleviated systemic inflammation in GA‐ONFH models. Additionally, curcumin decreased the apoptosis of osteocytes in the femoral heads and the ratio of GA‐ONFH in mice. Further, in vitro curcumin intervention inhibited M1‐type polarization via the Janus kinase1/2‐signal transducer and activator of transcription protein1 (JAK1/2‐STAT1) pathway. Taken together, this study demonstrates that curcumin is effective in preventing osteocyte apoptosis and the development of GA‐ONFH in a mouse model. Curcumin prevents inflammatory‐mediated apoptosis of osteocytes in part through inhibition of M1 polarization through the JAK1/2‐STAT1 pathway. These findings provide novel insights as well as a potential preventive agent for GA‐ONFH. This article is protected by copyright. All rights reserved. Abstract : During the development of steroid‐associated necrosis of the femoral head (SANFH), the infiltration of M1 cells in the femoral head and the expression of proinflammatory factors within the peripheral blood increased significantly, which may result in a subsequent enhancement of inflammatory‐induced osteocytes apoptosis. We determined that curcumin can reduce inflammatory‐induced osteocyte apoptosis in the early stage of SANFH. The protective effects of curcumin were mediated by inhibition of M1 polarization through the Janus kinase1/2‐signal transducer and activator of transcription protein1 (JAK1/2‐STAT1) signaling pathway.